Effect of Chewing Gum on Bowel Motility in Women Undergoing Post-Operative Cesarean Section - Abobaker, Randa Mohamed (International Journal of Innovative Research in Medical Science, 2018)
Postoperative paralytic ileus (POI) is one of the common problems after gynecologic surgery, occurring in 10-15% of postoperative women. Gum chewing helps patients regain bowel function faster and stay in the hospital for less time. Aim: The present study aimed to evaluate the effect of chewing gum on bowel motility in women undergoing postoperative cesarean section delivery. Research design: A quasi-experimental study design was used. Research setting: The study was conducted at the Postpartum Department of Maternity and Children’s Hospital. Sampling: A convenience sample size of 80 post-cesarean section women. Participants were divided into two equal groups: (40) the experimental (chewing gum) group, and (40) the control group (the hospital routine care). Tools: Three different tools were used to collect data.: Interview schedule for socio-demographic data and reproductive history (Tool I). Postoperative Assessment Sheet (Tool II). Gum chewing outcomes and length of stay in the hospital (tool III). Results: the mean timing of the first bowel sound was (1.05±2.25 &7.38±9.10 hour) for the experimental and the control groups; the mean timing of the first flatus was (& 3.50±4.47 8.12±8.6 hour) in both groups respectively. Also, the mean lengths of hospital stay among post-caesarian women were (1.05±2.25& 3.38±5.10 days) for both groups respectively. Conclusion: The use of gum chewing following post-Cesarean section delivery has beneficial effects in the prevention of POI in CS delivery and successively shortens the length of stay in the hospital. Recommendations: A counseling program should be developed for pregnant women during the antenatal care period for the prevention of postoperative ileus.